The use of insulin pumps as an innovative approach of diabetes therapy to improve glycemic control, patients’ comfort of life and daily activity. - Łazicka, Patrycja; Tarnowska, Julia; Jakubowska, Eliza (Journal of Education, Health and Sport, 2024)
Introduction and Purpose of Research. There are diverse types of insulin pumps available, such as traditional pumps with tubing, tubeless pumps or continuous glucose monitoring (CGM) systems, pumps with automated insulin suspension. Diabetes complications lead to raised death rates, and overall decreased quality of life among patients. The aim of the study is to examine the impact of insulin pump usage including the effects on glycemic control, quality of life and limitations in daily life. Our work aims to emphasize the importance of using appropriate therapies in patients with diabetes. Material and Methods. The review was based on the analysis of materials collected in the Google Scholar and, PubMed’’. The following keywords were entered during the search for scholarly articles: insulin pump, continuous glucose monitoring, quality of life, diabetes mellitus and insulin therapy. A total of 36 articles were considered for the study and verified for their relevance to the topic. Brief description of the state of Knowledge. The use of an insulin pump as an innovation can simplify tasks to manage the process and to maintain desired levels of blood glucose. Patients using a pump have more flexible possibilities regarding meals and diet. Additional non-health-related benefits, such as reduced worry about supplies while traveling, can significantly improve patients’ QoL as well activities, and community integration, as the pump aids in refining self-care habits. Conclusions. In this study, we investigated the impact of wearable technology of insulin pumps on metabolic management, the quality-of-life patients’ comfort of life and daily activity in children and adolescents with diabetes. The quality of life can substantially increase when the performances of advanced devices and algorithms are associated with considerable support from family and healthcare providers.